Sustainable Leadership and Green Innovation: The Role of Green HRM in Indonesian Export MSMEs - Lina Saptaria; Wawan Herry Setyawan; Danang Erwanto; Edwin Agus Buniarto; Arthur Daniel Limantara (Annals of Human Resource Management Research, 2026)
Purpose: Based on the Ability–Motivation–Opportunity (AMO) and Resource-Based View (RBV) frameworks, this study aims to analyze the direct and indirect relationships between Sustainability Leadership (SL), Green Human Resource Management (GHRM), and Green Innovation (GI) in export-focused MSMEs in Indonesia. Research Methodology: The research design was quantitative with a survey method. Data were selected through purposive sampling from 284 respondents. The research questionnaire used a five-point Likert scale. Data analysis used Structural Equation Modeling (SEM) with Partial Least Squares (PLS). Results: The findings indicate that Sustainable Leadership has no direct effect on Green Innovation, however, it has a significant effect on GHRM. Furthermore, GHRM significantly increases Green Innovation and is able to mediate the relationship between Sustainable Leadership and Green Innovation. Conclusions: The implementation of GHRM serves as a key factor that bridges Sustainability Leadership and Green Innovation within the context of export MSMEs. Limitations: This study only examines Sustainable Leadership, GHRM, and Green Innovation, without considering other variables such as organizational culture, government support, technology, and market pressures. Contributions: This study fills a research gap by integrating the AMO and RBV frameworks to explain the mechanism by which Sustainable Leadership influences Green Innovation through GHRM in the context of Indonesian export MSMEs, a finding that remains limited in the empirical literature. These findings highlight the importance of developing sustainable leadership programs, adopting GHRM practices, and encouraging green innovation to achieve sustainable performance among export MSMEs.